Role of Subcutaneous Bilirubinometre in the Evaluation of Bilirubin Level in Neonatal Jaundice - Maqsood, Almas; Zaidi, Syed Taqi Hasan; Saba, Ameena; Shujaat, Wasif; Fatima, Benish; Rao, Bushra (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To record the demographic features of neonates presenting with jaundice, identify their cause, and co-relate bilirubin levels obtained by subcutaneous bilirubinometre with a standard biochemical method.Study Design: Cross-sectional studyPlace and Duration of Study: Nursery of Combined Military Hospital, Malir Cantt Karachi, from Jul to Dec 2020.Methodology: A total of 100 cases of neonatal jaundice were enrolled using a systematic random sampling technique. The demographic data of enrolled neonates and risk factors for jaundice were recorded. Their bilirubin levels were recorded using transcutaneous bilirubinometre (TCB) JH-2. Serum bilirubin levels were analyzed at the same time and recorded.Results: Out of 100 neonates, 61(61 %) were male. Risk factors for jaundice included exaggerated physiological 70(70%), prematurity 11(11%), Rh incompatibility 9(9%), G6PD deficiency 5(5%). For all weight ranges, mean TCB values significantly correlated with mean serum bilirubin level (p-value